Spectrophotometric Estimation of Vitamin A in the Sturgeon Fish Liver of the Caspian Sea - Reza Hadjmohammadi, Mohammad; Javad Chaichi, Mohammad; Taghipour, Vali (Asian Journal of Chemistry, 2010)
Vitamin A present in sturgeon fish liver of Caspian sea was determined by Carr-Price reaction. In this reaction Vitamin A produces blue color (λmax = 620 nm) with SbCl3 in CHCl3 solution which is the basis for analytical measurement of this vitamin in visible region. The amount of this vitamin was in the range of 54080 ± 4234–76410 ± 5983 USP units (13524 ± 1059–22923 ± 1795 ppm)/g of fish liver oil for three different species of this fish.